Approaching Dissolved Species in Ammonoacidic GaN Crystal Growth: A Combined Solution NMR and Computational Study. Issue 31 (28th April 2020) - Becker, Peter; Wonglakhon, Tanakorn; Zahn, Dirk; Gudat, Dietrich; Niewa, Rainer
Abstract: Solutions of gallium trihalides Ga X 3 ( X =F, Cl, Br, I) and their ammoniates in liquid ammonia were studied at ambient temperature under autogenous pressure by multinuclear ( 71 Ga, 35 Cl, 81 Br) NMR spectroscopy. To unravel the role of pH, the analyses were done both in absence and in presence of ammonium halides, which are employed as mineralizers during ammonoacidic gallium nitride crystal growth. While gallium trifluoride and its ammoniate were found to be too sparingly soluble to give rise to a NMR signal, the spectra of solutions of the heavier halides reveal the presence of a single gallium‐containing species in all cases. DFT calculations and molecular dynamics simulations suggest the identification of this species as consisting of a [Ga(NH3 )6 ] 3+ cation and up to six surrounding halide anions, resulting in an overall trend towards negative complex charge. Quantitative 71 Ga NMR studies on saturated solutions of GaCl3 containing various amounts of additional NH4 Cl revealed a near linear increase of GaCl3 solubility with mineralizer concentration of about 0.023 mol GaCl3 per mol NH4 Cl at room temperature. These findings reflect the importance of Coulombic shielding for the inhibition of oligomerization and precipitation processes and help to rationalize both the low solubility of gallium halides in neutral ammonia solution and, in turn, the proliferating effect of the mineralizer during ammonoacidic gallium nitride formation. Abstract : Materials synthesis : A combination of solution NMR in liquid ammonia with quantum mechanical and molecular modelling allows identifying the dissolved species and their mineralizer concentration dependent solubility in ammonoacidic solutions with relevance for GaN crystal growth (see figure).